Implementing Pancasila Economic System through BUMDes: A Legal Analysis on Desa Empowerment and Indonesia's Legal Framework: Menerapkan Sistem Ekonomi Pancasila melalui BUMDes: Analisis Hukum tentang Pemberdayaan Desa dan Kerangka Hukum Indonesia - Jayantara, Made; Kurniawan, I Gede Agus (Rechtsidee, 2022)
This normative legal study aims to analyze the application of the Pancasila economic system in Desa through BUMDes. The research focuses on two legal issues: the urgency of implementing the Pancasila economic concept in Desa and constructing Indonesia's legal framework through BUMDes practices. The research results show that Desa requires empowerment and welfare improvement, making the implementation of the Pancasila economic system crucial. BUMDes is expected to implement the Pancasila values in its economic system and prioritize fair distribution of economic resources and community welfare. The legal construction of Indonesia through BUMDes practices can be done by adopting Pancasila economic values and principles of kinship and cooperation. The implication of this study is to encourage policymakers to promote the implementation of the Pancasila economic system and BUMDes practices in empowering Desa and constructing Indonesia's legal framework.Highlights Urgency of implementing Pancasila values in Desa for empowerment and welfare improvement. BUMDes as a means to implement Pancasila economic system and prioritize fair distribution of resources. Legal construction of Indonesia through adoption of Pancasila economic values and principles of kinship and cooperation. Keywords: Pancasila economic system, BUMDes practices, Desa empowerment, Legal framework, Fair distribution.